Prayers the devil answers : a novel - McCrumb, Sharyn, 1948- (Atria Books, 2016)
Suddenly thrust into the role of primary caretaker for her family following the tragic death of her husband, Ellie Robbins is appointed to serve out his term as sheriff of their rural Tennessee mountain town. The year is 1936, and her role is largely symbolic, except for the one task that only a sheriff can do: execute a convicted prisoner. Ellie has long proven she can handle herself. But becoming sheriff is altogether different, and the demands of the role are even more challenging when she is forced to combat society's expectations for a woman. Soon enough, dark secrets come to light, and Ellie must grapple with small town superstitions and the tenuaous ties she shared with a condemned killer as she carves out a place for herself in an uncertain future. --